An Overview of Self-Determination in Supporting Healthy Aging in Older Adults: A Narrative Review - Winarto, Agnestria (Journal of Rural Community Nursing Practice, 2025)
Introduction: The concept of healthy aging is strongly connected to self-determination theory, with older individuals engaging their sense of autonomy, skills, and social bonds to improve their overall quality of life. Aims: This review aims to determine the picture of self-determination in the older adults. Methods: Seven relevant study articles between 2011-2024 from PubMed, SpringerLink and BMC Geriatric were thematically review. Results: Self-determination in older adults, which includes autonomy, competence, and social connectedness, can decline due to factors such as physical frailty, cognitive impairment, and reliance on assistance. Intrinsic motivation and the fulfillment of psychological needs are key drivers in encouraging active participation of older adults in various activities. Beyond supporting independence, self-determination also directly enhances the physical, emotional, and social quality of life in older adults. Conclusions: Physical frailty, worsening health conditions, and cognitive decline may lead to a decrease in self-determination among older adults, yet their intrinsic motivation still plays a crucial role in driving active engagement. Recognizing these factors is vital for creating interventions that promote autonomy and enhance the overall well-being of elderly individuals.